DYNAMICS OF CHANGING THE DEATH PENALTY TO LIFE PRISON IN THE NEW KUHP - I Gede Bisma Edy Putra; Ida I Dewa Ayu Dwi Yanti; I Gusti Agung Ika Laksmi Mahadewi (International Journal Multidisciplinary (IJMI), 2026)
Objective: This study aims to analyze the regulation of the death penalty within the Indonesian criminal law system and to examine the conversion of the death penalty into life imprisonment from the perspective of sentencing objectives under the new Criminal Code. Method: This research employs normative legal research using statutory, conceptual, and comparative approaches. The collected materials are analyzed qualitatively through legal interpretation. Results: The findings indicate that the reformulation of the death penalty reflects a paradigm shift in Indonesian criminal law. The death penalty is no longer treated as an absolute principal punishment but as a special punishment whose execution may be postponed and converted into life imprisonment if the convicted person demonstrates positive behavioral changes during the probationary period. This reform implements the sentencing objectives stipulated in Article 51 of the 2023 Criminal Code, emphasizing public protection, offender rehabilitation, social reintegration, and the restoration of social balance. Novelty: Unlike the previous Criminal Code, which classified the death penalty as a principal punishment, the new Criminal Code recognizes it as a special punishment that may be converted into life imprisonment after the convicted person successfully completes a ten-year probationary period and fulfills certain legal requirements. Therefore, the conversion of the death penalty into life imprisonment represents a legal policy compromise that balances law enforcement, human rights protection, and the development of modern sentencing theory.